Interactions Between Nanoparticles and Dendritic Cells: From the Perspective of Cancer Immunotherapy - Jia, Jianbo; Zhang, Yi; Xin, Yan; Jiang, Cuijuan; Yan, Bing; Zhai, Shumei (Frontiers in Oncology, 2018)
Dendritic cells (DCs) are the primary antigen-presenting cells and play key roles in the orchestration of the innate and adaptive immune system. Targeting DCs by nanotechnology stands as a promising strategy for cancer immunotherapy. The physicochemical properties of nanoparticles (NPs) influence their interactions with DCs, thus altering the immune outcome of DCs by changing their functions in the processes of maturation, homing, antigen processing and antigen presentation. In this review, we summarize the recent progress in targeting DCs using NPs as a drug delivery carrier in cancer immunotherapy, the recognition of NPs by DCs, and the ways the physicochemical properties of NPs affect DCs’ functions. Finally, the molecular mechanisms underlying these effects are also discussed.